Mitigation of salinity induced negative impacts by salt tolerant plant growth promoting rhizobacteria Bacillus flexus in mustard (Brassica juncea L.) - Singh, Anjali; Prasad, Vishal (Frontiers in Microbiology, 2025)
Salinity is a major environmental stressor affecting crop productivity worldwide and a substantial portion of the agricultural ecosystem supporting cultivation of mustard (Brassica juncea L.) in Indian subcontinent is salinity stricken. However, plant growth promoting rhizobacteria has been noted to modulate salinity stress in plants through numerous direct and indirect mechanisms. Therefore, the present study was intended to determine the potential of a salt tolerant plant growth promoting rhizobacteria Bacillus flexus on alleviating the negative effects of salinity stress in mustard. The evaluation of germination percentage, growth parameters, and pigment content (chlorophyll and carotenoids) along with biochemical properties and antioxidant enzyme activities of mustard was studied by biopriming the seeds with Bacillus flexus both in absence and presence of salinity (100 mM NaCl) stress. The obtained results revealed a significant improvement in germination percentage and growth parameters (shoot length, root length, biomass and leaf area) of bioprimed mustard seedling both in presence and absence of salt stress. The biochemical properties such as pigment content, proline, total soluble protein, and total soluble sugar were found improved in bacterial treated seeds in comparison to control both in presence and absence of salinity stress. The percentage of electrolyte leakage and malondialdehyde (MDA) content was found decreased in bacterial treated plants under salinity induced condition as compared with non-treated plants. The antioxidant enzymes such as catalase (CAT), peroxidise (POX) and ascorbate peroxidise (APX) activities were found elevated in bacterial treated seeds in comparison to control both in presence and absence of salinity stress. The results obtained from the study revealed the protective and growth promoting abilities of Bacillus flexus against salinity stress. The bacterial strain used in the present study proved to be a promising candidate for improving mustard growth in soils challenged with salinity stress.